2019
DOI: 10.5194/hess-23-1763-2019
|View full text |Cite
|
Sign up to set email alerts
|

Oxycline oscillations induced by internal waves in deep Lake Iseo

Abstract: Abstract. Lake Iseo is undergoing a dramatic deoxygenation of the hypolimnion, representing an emblematic example among the deep lakes of the pre-alpine area that are, to a different extent, undergoing reduced deep-water mixing. In the anoxic deep waters, the release and accumulation of reduced substances and phosphorus from the sediments are a major concern. Because the hydrodynamics of this lake was shown to be dominated by internal waves, in this study we investigated, for the first time, the role of these … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…In comparison with the energies observed for the forced oscillations (i.e., for periods of 25.60 and 11.64 h), the energies associated with free baroclinic oscillations (i.e., periods of 7.11, 6.09 and 5.12 h shown in Tab. 1) were 1-2 orders of magnitude lower, where the highest among them (0.58 K 2 h) was found for a depth of 15 m and period of 6.09 h. This is in accordance with results of previous studies of Alpnacher See, Switzerland (Münnich et al, 1992), Sau reservoir, Spain (Vidal et al, 2005), Bromont Lake, Canada (Pannard et al, 2011) and Iseo Lake, Italy (Valerio et al, 2019) which show that higher vertical modes (i.e., forced baroclinic oscillations) dominate over the V1H1 mode (i.e., free baroclinic oscillations). The authors of these studies argue that the forced, higher vertical modes are more energetic due to the resonance between the periodic wind forcing and waves.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In comparison with the energies observed for the forced oscillations (i.e., for periods of 25.60 and 11.64 h), the energies associated with free baroclinic oscillations (i.e., periods of 7.11, 6.09 and 5.12 h shown in Tab. 1) were 1-2 orders of magnitude lower, where the highest among them (0.58 K 2 h) was found for a depth of 15 m and period of 6.09 h. This is in accordance with results of previous studies of Alpnacher See, Switzerland (Münnich et al, 1992), Sau reservoir, Spain (Vidal et al, 2005), Bromont Lake, Canada (Pannard et al, 2011) and Iseo Lake, Italy (Valerio et al, 2019) which show that higher vertical modes (i.e., forced baroclinic oscillations) dominate over the V1H1 mode (i.e., free baroclinic oscillations). The authors of these studies argue that the forced, higher vertical modes are more energetic due to the resonance between the periodic wind forcing and waves.…”
Section: Resultssupporting
confidence: 91%
“…In lakes and reservoirs, the most commonly observed mode is the V1H1 mode (e.g., Vidal et al, 2007;Simpson et al, 2011); however, the presence of higher vertical modes has also been reported (e.g., Münnich et al, 1992;Vidal et al, 2005Vidal et al, , 2007Vidal et al, , 2008Pannard et al, 2011;Simpson et al, 2011;Valerio et al, 2019), and it is even possible to reach the 5 th mode V5 (Vidal et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Previous applications of ELCOM are widely referenced in limnological studies (Trolle et al, 2012), including studies of reservoir hydrodynamics and sediment transport (Dissanayake et al, 2019;Trolle et al, 2012). AEM3D features in more recent publications describing reservoir and lake modeling (e.g., Madani et al, 2020;Ryu et al, 2020;Tranmer et al, 2018;Valipour et al, 2019;Valerio et al, 2019;Zamani & Koch, 2020). Zamani and Koch (2020) demonstrate the appropriateness of AEM3D for modeling reservoirs, such as Upper Yarra reservoir, that have complex bathymetry, steep walls, and a wind-mixed surface layer.…”
Section: Reservoir Hydrodynamics Modelmentioning
confidence: 99%
“…Internal waves drive baroclinic shear instabilities that enhance the vertical turbulent diffusivity and reduce the rate of dissolved oxygen depletion in the hypolimnion (Bouffard et al, 2014). Deep motions characterised by larger amplitudes at lower frequencies are favoured by the excitation of internal waves of the second vertical mode in strongly thermally stratified lakes (Valerio et al, 2019). Internal waves are a common response to wind forcing in not only large but also small stratified lakes (Boegman, 2009).…”
Section: Seasonal Variation In Sedimentation Cycle and Its Potential ...mentioning
confidence: 99%